Implementation of Open Innovation and Its Influence on Innovation Performance in Small and Medium Enterprises in Indonesia - Feby Syafitri (PT SOLUSI EDUKASI BERDIKARI, 2025)
This research aims to analyze the influence of open innovation implementation on innovation performance in small and medium enterprises (SMEs) in Indonesia. Open innovation is seen as an important strategy for SMEs in the face of market dynamics and increased global competition. This research uses a quantitative approach with a population of all SMEs in Indonesia that apply innovation in their business activities. Sampling techniques were carried out by purposive sampling, and data were obtained through questionnaires distributed to SME actors in various sectors. Data analysis was performed using multiple linear regression to examine the relationship between the variables of open innovation implementation and innovation performance. Results show that the application of open innovation has a positive and significant effect on improving the innovation performance of SMEs, especially through external collaboration, knowledge exchange, and the use of digital technology. These findings indicate that openness to resources and ideas from outside the organization can strengthen the competitiveness of SMEs in Indonesia. It is hoped that this research will serve as a reference for SME actors and policy makers in designing sustainable innovation strategies.